Yawning in acute anterior circulation stroke. Issue 11 (16th October 2007) - Singer, Oliver C; Humpich, Marek C; Lanfermann, Heiner; Neumann-Haefelin, Tobias
Abstract : Pathological yawning can be a clinical sign in disorders affecting the brainstem. Here we describe seven patients with pathological yawning caused by acute middle cerebral artery stroke, indicating that pathological yawning also occurs in supratentorial stroke. We hypothesise that excessive yawning is a consequence of lesions in cortical or subcortical areas, which physiologically control diencephalic yawning centres.